2019
DOI: 10.1101/592774
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A toolset of constitutive promoters for metabolic engineering ofRhodosporidium toruloides

Abstract: Background: Rhodosporidium toruloides is a promising host for the production of bioproducts from lignocellulosic biomass. A key prerequisite for efficient pathway engineering is the availability of robust genetic tools and resources. However, there is a lack of characterized promoters to drive expression of heterologous genes for strain engineering in R. toruloides. Results:Our data describes a set of native R. toruloides promoters, characterized over time in four different media commonly used for cultivation … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Fortunately, this issue can be overcome simply by measuring transgene copy number. For example, a direct comparison between the ANT and GAPDH promoters was made in this study and we observed that P ANT resulted in stronger GfKS expression than P GAPDH , in agreement with previous data comparing these promoters [32].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Fortunately, this issue can be overcome simply by measuring transgene copy number. For example, a direct comparison between the ANT and GAPDH promoters was made in this study and we observed that P ANT resulted in stronger GfKS expression than P GAPDH , in agreement with previous data comparing these promoters [32].…”
Section: Discussionsupporting
confidence: 92%
“…Similar maximum titers were reached following transformation of R. toruloides with the P ANT -GfKS and P GAPDH -GfKS constructs, even though the ANT promoter is natively stronger, as indicated by ANT transcript levels and reporter studies [32]. To test whether this relative difference in promoter strength also applies to expression of the heterologous KS, GfKS copy number, transcript levels, and protein levels were measured for selected GfKS strains (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…16 R. toruloides features many host characteristics vital for commercial-scale production, such as the capacity to grow to high cell densities, 17 the ability to utilize a wide range of nitrogen and carbon sources 18 and tolerance to inhibitory compounds found in unrefined substrates. 19 In addition to its native suitable industrial features, recent developments in the establishment of metabolic engineering tools and -omics techniques for R. toruloides [20][21][22][23][24] have not only enabled optimization of native bioproducts but also the ability to produce non-native bioproducts. While R. toruloides has successfully been engineered to produce heterologous products from pathways that natively have high carbon flux, like fatty acid-derived products 25 and nonnative terpenes, 26 R. toruloides has not been explored for the production heterologous NRPs.…”
Section: Introductionmentioning
confidence: 99%
“…The genes encoding fatty alcohol reductases (FARs) were codon optimized for R. toruloides based on a custom IFO0880 codon usage table. The FARs were cloned under the control of a GAPDH promoter (JBEI registry: JPUB_013267; nourseothricin resistance) or an ANT1 promoter (JBEI registry: JPUB_013283; hygromycin resistance) and inserted into plasmid pGI2 (Nora et al, 2019). The FAR expression cassettes were then introduced into R. toruloides via Agrobacterium tumefaciens‐ mediated transformation (ATMT).…”
Section: Methodsmentioning
confidence: 99%